The genus Leucophenga (Diptera, Drosophilidae), part I: the abbreviata species group from the Oriental region with morphological and molecular evidence - Su, Yirui; Lu, Jinming; Chen, Hongwei (Zootaxa, 2013)
A new species group, the abbreviata group is established within the genus Leucophenga based on one known and three new species, all of which are endemic to the Oriental region: L. abbreviata (de Meijere, 1911), L. brevivena sp. nov., L. sujuanae sp. nov. and L. zhenfangae sp. nov. A key to four species of the abbreviata group and the DNA barcoding are provided. Twenty-three mtDNA COI sequences belonging to the above species are analyzed; the molecular data are used as interactive evidence to evaluate the species boundaries defined by the morphological data.